2021
DOI: 10.1002/hbm.25595
|View full text |Cite
|
Sign up to set email alerts
|

Relating quantitative 7T MRI across cortical depths to cytoarchitectonics, gene expression and connectomics

Abstract: Ultra-high field MRI across the depth of the cortex has the potential to provide anatomically precise biomarkers and mechanistic insights into neurodegenerative disease like Huntington's disease that show layer-selective vulnerability. Here we compare multi-parametric mapping (MPM) measures across cortical depths for a 7T 500 μm whole brain acquisition to (a) layer-specific cell measures from the von Economo histology atlas, (b) layer-specific gene expression, using the Allen Human Brain atlas and (c) white ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…In addition, atlas matching of high resolution neurophysiological findings to modern neuroimaging and/or postmortem human neuroanatomy may provide intermediate steps for mechanistic explanations ( Tokariev et al, 2021 ). They can be also interpreted using fundamental principles that appear to link different scales of neuronal activity, structure, and expression patterns ( Gao et al, 2020 ; McColgan et al, 2021 ; Tokariev et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, atlas matching of high resolution neurophysiological findings to modern neuroimaging and/or postmortem human neuroanatomy may provide intermediate steps for mechanistic explanations ( Tokariev et al, 2021 ). They can be also interpreted using fundamental principles that appear to link different scales of neuronal activity, structure, and expression patterns ( Gao et al, 2020 ; McColgan et al, 2021 ; Tokariev et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, before disease onset, the striatal atrophy and loss of corticostriatal white matter occur with succeeding cell death in the cortex in the later stage of the disease ( 52 , 53 ). Thus, a stereotypical pattern of neurodegeneration and neuron loss occurs in HD ( 54 , 55 ), but whether it involves mHTT spreading is unknown. Consistent with earlier work ( 56 ), we showed that mHTT can be transported by TNT-like protrusions and that Rhes, which strongly interacts with mHTT ( 7 ), accelerates this process several fold ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different T2 * distributions across layers would lead to slightly different results. A more complex laminar T2 * distribution, e.g., the one observed by McColgan et al (2021) with a rapid drop of T2 * in the outermost layer likely due to superficial veins, leads to a contrast increase between CSF and superficial GM. This would further slightly amplify the effects predicted by our simulations, especially in fMRI sequences employing longer echo times like BOLD fMRI.…”
Section: Functional Magnetic Resonance Imaging Simulationsmentioning
confidence: 94%
“…Proton density values and relaxation times at 7 Tesla for CSF, WM and cortical layers (see also Table 2 ) were taken from the literature ( Rooney et al, 2007 ; Tofts, 2010 ; Carey et al, 2018 ; Caan et al, 2019 ; McColgan et al, 2021 ) and mapped to the mechanical gyrus model.…”
Section: Methodsmentioning
confidence: 99%